Foreign Direct Investment and Sustainable Development in the New EU Member States: Environmental Aspects - Witkowska, Janina (Comparative Economic Research. Central and Eastern Europe, 2012)
The aim of this paper is to examine the potential impact of foreign investors' activities on the environment of the new European Union's Member States and discuss a role of a common environmental policy and member states' policies towards foreign investors. The analysis embraces three new EU countries, namely the Czech Republic, Poland and Slovakia. The scope of the analysis are years 1997- 2007. The subject of the analysis is the sector and branch structure of FDI stock in the new EU Member States with special reference to FDI located in pollution-intensive industries which are selected according to the UNCTAD classification. Both the OECD and national data base of statistics is used to calculate the share of foreign investors' involvement in pollution-intensive activities in the new UE Member States. The research results show that as yet there has been no empirical evidence that FDI has a particularly negative impact on the natural environment in the new EU Member States.